2017
DOI: 10.1017/s0033291717001660
|View full text |Cite
|
Sign up to set email alerts
|

The association between adolescent psychopathology and subsequent physical activity in young adulthood: a 21-year birth cohort study

Abstract: Our findings suggest that there is no longitudinal association between adolescent psychopathology and PA in young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
7
0
2
Order By: Relevance
“…Mental health problems at age 16 were assessed using the Youth Self-Report (YSR) questionnaire that includes measures for attention and behavioural problems 15 and has been established as a data collection method in epidemiological research. [16][17][18] In this study, we used three of the eight symptom subscales: anxiety and depression (13 items), attention problems (7 items), and social problems (10 items), as these were regarded the most relevant to assess mental health at this age. All items for each subscale are presented in supplemental material.…”
Section: Mental-health Related Predictorsmentioning
confidence: 99%
“…Mental health problems at age 16 were assessed using the Youth Self-Report (YSR) questionnaire that includes measures for attention and behavioural problems 15 and has been established as a data collection method in epidemiological research. [16][17][18] In this study, we used three of the eight symptom subscales: anxiety and depression (13 items), attention problems (7 items), and social problems (10 items), as these were regarded the most relevant to assess mental health at this age. All items for each subscale are presented in supplemental material.…”
Section: Mental-health Related Predictorsmentioning
confidence: 99%
“…Even when analyzed by gender, there was no association between the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 two variables in either sex in the present cohort. Furthermore, Suetani et al (2018) recently found no longitudinal association between adolescent psychopathology at age 14 and PA status at age 21 using the same dataset. The current findings build on to the previous study in that they suggest even those with CMDs in young adulthood are not disadvantaged from engaging in PA in the future.…”
Section: Discussionmentioning
confidence: 93%
“…PA levels combined) versus high (high IPAQ PA level only). In keeping with previous research using the Mater-University of Queensland Study of Pregnancy cohort (Suetani et al, 2018), responses to a range of questions relating to general measures of frequencies and types of PA were used to estimate the PA engagement at the 21 year follow-up. In this self-report, vigorous exercise was defined as 'exercise which makes you breathe harder or puff and pant'.…”
Section: Measurement Of Physical Activity Statusmentioning
confidence: 99%
“…Emocionalmente, conlleva una anticipación entusiasta y de ansiedad por el futuro, junto con sentimientos de nostalgia o frustración e importantes reajustes psicológicos (Sha-pero et al, 2015). Un período decisivo en el desarrollo de la madurez, donde se construyen los procesos autónomos de adquisición de hábitos que permiten el equilibrio saludable, que prevengan el desarrollo de trastornos clínicos asociados como depresión (Hankin et al, 2015;Guillén, Montaño, Fernández, Gordillo, & Solanes, 2013;Polanczyk, Salum, Sugaya, Caye, & Rohde, 2015;Suetani et al, 2017), trastornos adictivos, ansiedad y estrés o agresividad (Joshi, & Yadav, 2017;Páramo, 2011;Vangberg, 2013) tendencias autodestructivas, entre otros procesos desadaptativos (Gartstein, Slobodskaya, Zylicz, Gosztyla, & Nakagawa, 2010;Lombas, Martín-Albo, Valdivia-Salas, & Jiménez, 2014;López-Soler, Alcántara, Fernández, Castro, & López-Pina, 2010). Cloninger (2003), propone en su Modelo Psicobiológico de Personalidad la existencia de "causas internas que subyacen al comportamiento individual y a la experiencia de la persona" (Cloninger, 2003, p.3), buscando integrar el substrato biológico de la personalidad con el desarrollo producido por la experiencia y el aprendizaje socio-cultural (García, 2012).…”
unclassified